Imaging Tumor Metabolism Using In Vivo Magnetic Resonance Spectroscopy. Issue 2 (March 2015) - Li, Yan; Park, Ilwoo; Nelson, Sarah J
Abstract : Abstract: Magnetic resonance spectroscopy (MRS) is a powerful tool for noninvasively investigating normal and abnormal metabolism. When used in combination with imaging strategies, multinuclear MRS methods provide detailed biochemical information that can be directly correlated with anatomical features. Hyperpolarized 13 C MRS is a new technology that reflects real-time metabolic conversion and is likely to be extremely valuable in managing patients with cancer. This article reviews the use of in vivo 31 P, 1 H, and 13 C MRS for assessing cancer metabolism in order to provide information for diagnosis, planning treatment, assessing response to therapy, and predicting survival for patients with cancer.